Analysis of the effect of daily stress on the skin and search for genetic loci involved in the perceived stress of an individual. Issue 3 (1st April 2022) - Inoue, Yu; Hasebe, Yuichi; Igarashi, Toshio; Kawagishi‐Hotta, Mika; Okuno, Ryosuke; Yamada, Takaaki; Hasegawa, Seiji
Abstract: Background: Stress may have various effects on our bodies. In particular, the skin may be readily influenced by stress. In addition, there are individual differences in the way we feel stress, suggesting the involvement of genetic factors in such individual differences. Objectives: In this study, we analysed the influence of stress on skin condition and ageing involving Japanese females, and investigated single nucleotide polymorphisms (SNPs) that influence perceived stress of an individual. Methods: We collected genotype data from 1200 Japanese females. At the same time, a questionnaire was conducted on the degree of stress that each subject feels on a daily basis and the current skin condition. We analysed the effects of stress on skin condition and searched for SNPs related to individual stress susceptibility by genome‐wide association studies. Results: Our data suggested that stress influences skin condition and ageing, as previously reported. And, we found rs74548608 as a SNP that affects perceived stress of an individual. This SNP is located on the upstream of Patched‐1, which is a gene that functions as a sonic hedgehog receptor. Conclusions: Our study has identified new genetic factors for perceived stress of an individual in the Japanese female. The SNP found in this study may be a candidate factor important for understanding the perceived stress of an individual of Japanese. Abstract :